Cybersecurity awareness among the National Intelligence Agency’s government officials: perception and internal organizational environment - Boonyawarit, Aroot; Hemaphan, Pornphan (Mahachula Academic Journal, 2024)
This study has 3 objectives: (1) to describe the level of cybersecurity awareness among the National Intelligence Agency’s (NIA) government officials (2) to compare factors affecting the cybersecurity awareness, classified by demographical and perception factor and (3) to investigate the relationships between internal organizational environment and cybersecurity awareness. The data was collected from ๒๖๐ samples of NIA’s government officials. The statistics were presented in percentage, mean, and standard deviation, One - Way ANOVA and Pearson’s Correlation Coefficient. The results showed that (1) the overall level of cybersecurity awareness among the NIA’s government officials was at the highest level. (2) The demographical factors, namely education, career fields and cybersecurity training experience as well as perception factors were found statistically significant difference at .05 level of significance. And (3) there was a positive relationship between internal organizational environment factors and cybersecurity awareness (r = .717, p < .01).